AKIBAT HUKUM PENGALIHAN HAK ATAS MEREK TERDAFTAR BERDASARKAN AKTA HIBAH WASIAT - Pramurti, Rifzki Dhiah (Notarius, 2018)
Abstract The transfer of rights to a trademark is provided in Article 41 paragraph (1) of Law Number 20 of 2016, in which case the right to a registered mark may be transferred or transferred because of a grant of a will, in which case after the transfer of title to the mark takes place, Submission. The transfer of rights to a mark by an authentic deed made by a Public Official or Notary has legal certainty with the anatomy of the deed in accordance with the provisions of Article 38 of Law Number 2 of 2014 concerning Notary Position. Insofar as the contents of the transfer agreement of the grant will not be denied by the parties, the deed shall have the perfect proof power to be used as evidence in the Court. The transfer of Right to Trademark to another person has the consequence that the recipient of the right of a mark shall be obligated to administer and finance the recording of the transfer of rights to the mark officially to the Directorate of Trademark, Directorate General of Intellectual Property, in the event of a transition through the grant, the original owner of the mark shall provide the original certificate Brands and power of attorney to regulate the application for the transfer of rights to the mark.   AbstrakPengalihan hak atas merek diatur di dalam Pasal 41 ayat (1) Undang- Undang Nomor 20 Tahun 2016, yang dalam hal ini hak atas merek terdaftar dapat beralih atau dialihkan karena hibah wasiat yang dalam hal ini setelah pengalihan hak atas merek terjadi, harus diikuti dengan penyerahan. Pengalihan hak atas merek dengan akta otentik yang dibuat oleh Pejabat umum atau Notaris memiliki kepastian hukum dengan anatomi akta yang sesuai dengan sebagaimana diatur didalam pasal 38 Undang-undang Nomor 2 tahun 2014 tentang tentang Jabatan Notaris. Sejauh isi perjanjian pengalihan hibah wasiat tersebut tidak dapat disangkal oleh para pihak, maka akta tersebut memperoleh kekuatan pembuktian yang sempurna untuk dijadikan alat bukti di Pengadilan. Peralihan Hak atas Merek kepada orang lain memiliki konsekuensi bahwa penerima hak merek wajib untuk mengurus dan membiayai pencatatan pengalihan hak atas merek secara resmi ke Direktorat Merek, Direktorat Jendral Hak Kekayaan Intelektual, dengan adanya peralihan melalui hibah wasiat tersebut, maka pemilik awal merek memberikan sertifikat asli merek dan surat kuasa utuk mengatur permohonan penyerahan hak atas merek.